Textures and fabrics of 700-m deep ice core obtained at Mizuho Station, East Antarctica - Narita, Hideki; Nakawo, Masayoshi; Fujii, Yoshiyuki (1986)
P(論文) Crystal grain-areas and shape factors of a 700-m deep ice core obtained at Mizuho Station (70°41.9′S, 44°19.9′E), Antarctica, in 1983-1984 were measured from photographs of thin sections taken in crossed polarized light within a month after the core recovery. Also, c-axis orientations were examined with the sections at selected depths in situ. Comparison of the data with those of the Camp Century, Dye III and Byrd Station cores indicated the ice of the late Wisconsin might be existing at depth below about 520m at Mizuho Station. departmental bulletin paper